Optimizing nitrogen and mineral composition of the highly concentrated mash of raw starch - Kuts, Anatoly; Mudrak, Tatiana; Kovalchuk, Svitlana (My University, 2016)
For yeast cultivation race used the yeast Saccharomyces cerevisiae DO-11 corn mash with a concentration of 20 and 26% solids, amino nitrogen concentration was adjusted by making the wort amino acids glycine and urea.The use of zinc ions and magnesium in step yeast generation possible to obtain seeding yeast with increased physiological of up to 500m/cm³ and shorten the duration yeast generation to 12 hours. It is proved that the addition of metal nanoparticles in ionic form and should be carried out cyclically at a ratio of 2-3 cycles of metal, and as much without metals.Thus, based on the studies identified the optimal concentration of nitrogen and mineral nutrition by culturing yeast to obtain a large number of physiologically active yeast for fermentation of wort of high concentrations. Для культивування дріжджів використовували расу дріжджів Saccharomyces cerevisiae ДО-11, сусло із кукурудзи концентрацією 20 і 26 % СР, концентрацію амінного азоту коригували шляхом внесення в сусло амінокислоти гліцин та карбаміду. Використання іонів цинку і магнію на стадії дріжджегенерування дозволило отримати засівні дріжджі з підвищеною фізіологічною в кількості до 500 млн/см3 та скоротити тривалість дріжджегенерування до 12 годин. Доведено, що додавання металів у нано- та іонній формі потрібно проводити циклічно у співвідношенні 2-3 цикли з металами, та стільки ж без металів. Таким чином, на основі проведених досліджень визначені оптимальні концентрації азотного та мінерального живлення при культивуванні дріжджів з отриманням великої кількості фізіологічно активних дріжджів для зброджування сусла високих концентрацій.
Keywords: висококонцентроване сусло; сухі речовини; мінеральне живлення; азотне живлення; зброджування; цинк; магній; метали в наноформі; high concentrated wort; dry matter; mineral nutrition; nitrogen nutrition; fermentation; Zinc; Magnesium; metals in nanoform; кафедра біотехнології продуктів бродіння і виноробства; кафедра готельно-ресторанної справи